Failure analysis of bond pad metal peeling using FIB and AFM - Tan, Cher Ming (2009)
Aluminum bond pads on semiconductor chips play an important role in chips functionality and reliability. Bond pad peeling during wire bonding process results in yield reduction. The failure mechanisms of the peeling must be identified so that potential reliability problem of poor bond pad adhesion can be avoided. In this work, FIB, SEM, EDX, and AFM are used to identify the root causes of the peeling. The possible root causes are found to be the presence of an extra layer of thickness of 0.14 µm and the poly-silicon surface roughness asperity due to prolonged BOE etching time.